Room 216 - Dutt, Mignon Bravo (Penguin Random House SEA, 2023)
Room 216 is about four strong female characters and their complex experiences. It tells the story of university roommates, each with a unique motivation and struggle. After graduation, Sandy, Tintin, Serene, and Issa embark on separate journeys that take each to different parts of the world. Following several relocations, Tintin now lives in America, ten thousand miles away from her ancestral home in the Philippines, but one that she keeps revisiting because it houses all her memories and has been the only permanent home she’s known. But her mother and sister now want to put the property for sale. Sandy, now based in Singapore, is an achiever who wants both career and family, but soon faces a marital crisis that may also threaten her most important role: being a mother. Serene is a doctor in Manila who realizes how life, in its real essence, is truly short. This awareness emboldens her to follow her heart, even if it means shunning her traditional Chinese family. Issa is simply stunning. She loves every inch of her beautiful body for the strength it gives her and for making her capable. But she is diagnosed with a disease that requires surgery and she must now come to terms with the attendant scar and the sense of incompleteness.